2023
DOI: 10.1038/s41598-023-29284-7
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of early gastric cancers by texture and color enhancement imaging using a high-definition ultrathin transnasal endoscope

Abstract: We evaluated whether texture and color enhancement imaging (TXI) using a high-definition ultrathin transnasal endoscope (UTE) improves the visibility of early gastric cancer (EGC) compared with white-light imaging (WLI). This study included 31 EGCs observed by TXI mode 2 using a high-definition UTE prior to endoscopic submucosal dissection. The first outcome was to compare the color differences based on Commission Internationale de l’Eclairage L*a*b* color space between EGCs and the surrounding mucosa by WLI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Dobashi et al ., 25 Abe et al ., 26 Koyama et al ., 27 and Okimoto et al 28 . reported TXI mode1 can enhance color changes and improve the visibility of SCC suspicious lesions in the pharynx and esophagus, gastric cancer, and superficial nonampullary duodenal tumor compared to WLI.…”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dobashi et al ., 25 Abe et al ., 26 Koyama et al ., 27 and Okimoto et al 28 . reported TXI mode1 can enhance color changes and improve the visibility of SCC suspicious lesions in the pharynx and esophagus, gastric cancer, and superficial nonampullary duodenal tumor compared to WLI.…”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 99%
“…TXI is a new image-enhanced endoscopy that enhances brightness, surface irregularities such elevation or depression, and subtle color changes. Dobashi et al, 25 Abe et al, 26 Koyama et al, 27 and Okimoto et al 28 reported TXI mode1 can enhance color changes and improve the visibility of SCC suspicious lesions in the pharynx and esophagus, gastric cancer, and superficial nonampullary duodenal tumor compared to WLI.…”
Section: Endoscopic Diagnosis Of Duodenal Epithelial Tumorsmentioning
confidence: 99%
“…Moreover, the majority of GA‐FG are small and have a similar or pale color in comparison to surrounding mucosa with poorly demarcated borders, which may increase the difficulty in detection of these lesions 2,3 . TXI is a novel image enhancement technique, which increases the difference in contrast in surface morphology and color of the mucosa and has the potential to improve the detection of superficial lesions in the stomach 4–6 . TXI combines retinex‐based processing modifications and color enhancements to enhance texture, brightness and color in an image, while maintaining image naturalness seen in WLI 7 .…”
Section: Figurementioning
confidence: 99%
“…2,3 TXI is a novel image enhancement technique, which increases the difference in contrast in surface morphology and color of the mucosa and has the potential to improve the detection of superficial lesions in the stomach. [4][5][6] TXI combines retinex-based processing modifications and color enhancements to enhance texture, brightness and color in an image, while maintaining image naturalness seen in WLI. 7 This image enhancement technology has been proposed to improve detection of subtle tissue differences, such as that seen in GA-FG, where the superficial layer is covered with non-neoplastic epithelium, 2 resulting in no clear demarcation line, microsurface or microvessel irregularity.…”
mentioning
confidence: 99%
“… 17 The effectiveness of TXI compared with WLI in improving the visibility of gastric and colorectal cancer has been reported. 18 , 19 , 20 , 21 , 22 , 23 Improved visibility on TXI for ESCC has also been reported 24 ; however, the effects of TXI when iodine staining is used for ESCC have not been evaluated. Here, we preliminary examined the effects of TXI on improving the endoscopic visibility of ESCC under 1% iodine staining.…”
Section: Introductionmentioning
confidence: 99%